2021
DOI: 10.1108/meq-09-2020-0212
|View full text |Cite
|
Sign up to set email alerts
|

Is the choice of less-polluting modes of transport for non-work purposes affected by socio-demographic factors? Evidence from India

Abstract: PurposeUsing survey data of a developing country city, this study aims to examine the impact of different socio-demographic factors on the choice of less-polluting modes of transport for purposes other than work.Design/methodology/approachStratified random sampling technique is employed and data on socio-demographic characteristics and mode of transport used is collected. Descriptive statistics complemented with a logit model of choice probabilities is implemented on the data obtained.FindingsMajority of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…These findings are in accordance with the observations of Anand and Tiwari (2007), Mahadevia and Advani (2016), Saigal et al. (2020, 2021a, 2021b), Srinivasan and Rogers (2005), Yang et al (2017), Jain and Tiwari (2020), and Li et al. (2018) but do not support the hypotheses proposed by Korzhenevych and Jain (2018), and Tilley and Houston (2016).…”
Section: Resultssupporting
confidence: 81%
“…These findings are in accordance with the observations of Anand and Tiwari (2007), Mahadevia and Advani (2016), Saigal et al. (2020, 2021a, 2021b), Srinivasan and Rogers (2005), Yang et al (2017), Jain and Tiwari (2020), and Li et al. (2018) but do not support the hypotheses proposed by Korzhenevych and Jain (2018), and Tilley and Houston (2016).…”
Section: Resultssupporting
confidence: 81%
“…Several studies reported that the chemical and biological elements may be altered by PM concentration mainly PM 2.5 which diffuses into sensitive regions of the respiratory system and may cause multiple allergies and respiratory illnesses and premature mortality (Wu et al 2020 ). Jaipur is one of the fastest-growing urban cities in India thus influenced with high traffic obstruction and industrial emissions that increase the air pollution (Saigal et al 2021 ). On the other hand, high temperature and high wind speed increase the dispersion of particulate pollutants in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…The environmental quality index is an index that provides an overview of sociodemographic and environmental activities through the environmental capacity support managed by government agencies, budget allocations, regional regulations, human resources, and infrastructural facilities [31,32]. The environmental quality index model entails inputs and outputs in the components that support the ecological balance mechanism [33].…”
Section: The Relativity Of Oil Palm Expansion To Intragenerational Dy...mentioning
confidence: 99%